Kepemimpinan Perempuan Dalam Perspektif Islam Di SMA Muhammadiyah Pamijahan Bogor - Lestari, Lilis; Rahmawati, Ima; Ihsan, Muzhir (JURNAL KAJIAN ISLAM MODERN, 2023)
Women's leadership is still taboo for some parts of society, because they still think that women are not as great and strong as men. However, the changing times provide new facts that women can lead like men and even exceed them, because women are more multitalent, more empowering, more communicative, exemplary, compassionate and motherly, intelligent and conscientious and responsible. Theologically there is no difference between women and men in terms of leadership because each has a different role according to their nature. In this study the authors try to explain how women's leadership in the Islamic perspective towards the Principal at SMA Muhammadiyah Pamijahan Bogor with a qualitative approach research method based on three stages of data analysis, namely Data Reduction (data reduction), Data Display (data display), and Verification (conclusion drawing). ) or commonly referred to as data triangulation, namely combining various existing data and sources. From this research, it shows that female leaders in the Islamic Prespective at Muhammadiyah High School are able to set an example and always strive to advance the educational institutions they lead and this can be seen from the development of both the quality of facilities and infrastructure as well as the quantity of students who continue to increase in number.